Crustose coralline algal growth, calcification and mortality following a marine heatwave in Western Australia. (1st September 2015) - Short, Jessie; Foster, Taryn; Falter, James; Kendrick, Gary A.; McCulloch, Malcolm T.
Abstract: Crustose coralline algae (CCA: Corallinaceae, Rhodophyta) are ubiquitous components of many benthic habitats and play a critical ecological role by contributing significantly to their structural complexity and diversity. During the austral summer of 2010–2011 a "marine heatwave" severely impacted marine communities along the coast of Western Australia (WA). The heatwave was characterised by anomalously high seawater temperatures throughout that summer and, to a lesser extent, for the two summers thereafter. To investigate coralline algal response to heating we measured growth, calcification and mortality rates for Hydrolithoideae CCA at Marmion Lagoon off of Perth, WA, from winter 2011 to winter 2013, directly following the 2010–2011 heatwave. Seawater carbonate chemistry and temperature were also measured to facilitate a more complete understanding of the various drivers of coralline algal metabolism. Extension and calcification rates were generally within the expected ranges, however, normal seasonal patterns were not observed. Instead, there was a distinct lack of seasonality in growth rates and high rates of mortality during summer suggesting that these coralline algae were experiencing stress, which was likely related to anomalously high seawater temperatures. Our results indicate that Western Australian CCA are susceptible to prolonged heating events, and the extent of their vulnerability may be dependant on species-specific tolerance levels as well as additional ecological and environmental factors. Graphical abstract: Highlights: We investigated Hydrolithoideae CCA following a marine heatwave off of Perth, WA. High mortality rates were observed when temperatures were high. The expected increase in growth rates from winter to summer was not observed. High mortality and unexpected seasonality are indicative of thermal stress. These results have important implications for coral reefs in the near future.